STUDENT PERCEPTIONS OF USING LINGOPANDA APPLICATION TO IMPROVE PRONUNCIATION SKILLS - Fadia Rezky Amelia; Seny Luhriyani Sunusi; Asriati (International Journal of Business English and Communication, 2026)
In today’s era of globalization, English plays a crucial role as a means of international communication and interaction. One of the main challenges in mastering English is pronunciation. This study aims to explore students’ perceptions of the use of the LingoPanda application in improving English pronunciation, as well as to examine how this application helps them overcome pronunciation difficulties. A qualitative method was employed, with data collected through interviews with BEC students from the 2021–2023 cohorts who have used the LingoPanda application. Thematic coding was used for data analysis. The findings reveal that students have a positive perception of using the LingoPanda application. It is considered practical, easy to use, and supportive of independent learning. Students feel more confident in speaking English as they can practice anytime without embarrassment. Features such as immediate feedback and native pronunciation models help students become more aware of their pronunciation errors, improve fluency, and apply accurate pronunciation in real-life speaking contexts.